1999
DOI: 10.1136/oem.56.4.237
|View full text |Cite
|
Sign up to set email alerts
|

Short-term associations between outdoor air pollution and mortality in London 1992-4.

Abstract: Objectives-A previous study of the short term eVects of air pollution in London from April 1987 to March 1992 found associations between all cause mortality and black smoke and ozone, but no clear evidence of specificity for cardiorespiratory deaths. London data from 1992 to 1994 were analysed to examine the consistency of results over time and to include particles with a mean aerodynamic diameter of 10 µm (PM 10 ) and carbon monoxide. Methods-Poisson regression was used of daily mortality counts grouped by ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 19 publications
4
52
2
3
Order By: Relevance
“…These observations are consistent with those reported by Bremner et al (29) in London: the effects increased from lag-day 0 to a maximum at lag-day 1 for NO 2 , SO 2 , and PM 10 .…”
Section: Discussionsupporting
confidence: 83%
“…These observations are consistent with those reported by Bremner et al (29) in London: the effects increased from lag-day 0 to a maximum at lag-day 1 for NO 2 , SO 2 , and PM 10 .…”
Section: Discussionsupporting
confidence: 83%
“…For the other two age categories, ages 0-14 and 15-64 years, results were available from three studies conducted in London (Atkinson et al, 1999), West Midlands (Bremner et al, 1999) and Rome (Michelozzi et al, 2000) (Tables A4). Together these cities represent a population in excess of 10 million people. A meta-analysis of results from these three cities gave summary estimates of 1.010 (0.998, 1.021) and 1.008 (1.001, 1.015) per 10 µg/m 3 increases in PM 10 for respiratory admissions, ages 0-14 and 15-64 years respectively.…”
Section: Hospital Admissions and Particlesmentioning
confidence: 99%
“…An epidemiologic study in the Netherlands showed that exposure to diesel exhaust particles, measured as either truck traffic density or classroom black smoke concentrations, was significantly associated with reduced lung function and increased prevalence of chronic respiratory symptoms in school children (26,27). In addition, deaths from cardiovascular disease in European cities have been associated with ambient concentrations of black smoke, for which the major source is diesel-powered vehicles, with the effect estimates of black smoke being more stable than those for PM 10 (21,28).…”
Section: Pneumonia Coefficientmentioning
confidence: 99%